The Effect of Training and Career Development on Employee Performance at PT. Shitong International Technology - Anugrah Anggun Sentosa; Ida Ayu Made Er Meytha Gayatri; Yun Fitriano (Utami Publisher, 2026)
This study aims to determine and analyze the influence of Training (X1) and Career Development (X2) on Employee Performance (Y) at PT. Shitong Internasional Teknologi in South Bengkulu. Rapid technological developments require this telecommunications equipment distributor to have competent human resources with high motivation through clear career paths.The research method used is quantitative. The population in this study were all 30 employees of PT. Shitong Internasional Teknologi, where the entire population was used as respondents (saturated sample). Data were collected through questionnaires that had been tested for validity and reliability. Data analysis techniques used Multiple Linear Regression Analysis, Hypothesis Testing (t-test and F-test), and Coefficient of Determination (R2) with the help of SPSS software. The results showed that: (1) Training has a positive and significant effect on employee performance, with a regression coefficient of 1.015 and a significance value of 0.000. (2) Career Development has a positive and significant effect on employee performance with a significance value of 0.001. (3) Simultaneously, Training and Career Development have a significant effect on employee performance, as evidenced by the F-test significance value of 0.000. The Adjusted R Square value of 0.996 indicates that the contribution of the independent variables in explaining the dependent variable is 99.6%, while the remaining 0.4% is explained by other factors outside this study.